2012
DOI: 10.1016/j.compind.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable enterprise interoperability from the Activity Domain Theory perspective

Abstract: The investigation of sustainable enterprise interoperability requires an explicit position of what constitutes the enterprise. In particular, human aspects like agency, sense-making, interpretation, common understanding, etc., must be taken into account. To this end, the purpose of this contribution is to make an inquiry into interoperability from the perspective of the Activity Domain Theory (ADT). In this theory, the enterprise is considered as a constellation of activity domains. The activity domain is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several international research initiatives have shown a considerable progress in EI over the last years [16]. Developments on enterprise architectures for modelling and engineering, model-driven [26,27]. Indeed, following Holland's perspective, adaptation also builds complexity [28].…”
Section: Concerns On Eis Engineering and Interoperability: A Technolomentioning
confidence: 99%
“…Several international research initiatives have shown a considerable progress in EI over the last years [16]. Developments on enterprise architectures for modelling and engineering, model-driven [26,27]. Indeed, following Holland's perspective, adaptation also builds complexity [28].…”
Section: Concerns On Eis Engineering and Interoperability: A Technolomentioning
confidence: 99%
“…This is in line with the view of pragmatism that research should be made to change and make life better. 34 This last point is important in the field of interpersonal communication and family therapy, where Cronen's own Practical Theory, Coordinated Management of Meaning (CMM) is mostly used.…”
Section: Type Of Knowledge Contribution Descriptionmentioning
confidence: 99%
“…Description dualism of practitioner and theorist as well between professional and participant 34 . This view is shared by many other scholars such as Donald Schön [124] and Bengt Molander.…”
Section: Type Of Knowledge Contributionmentioning
confidence: 99%
See 2 more Smart Citations